Analisis Dampak Digital Payment pada Pengendalian Internal Penerimaan di Hotel Grand Hyatt Bali - Ni Kadek Mulia Dewi; I Gusti Ngurah Agung Wiryanata; Luh Nyoman Tri Lilasari (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
The purpose of this investigation is to analyze the influence of digital transaction methods on the control mechanisms of cash revenue at the Grand Hyatt Bali Hotel. The study applies a qualitative descriptive design, where information is gathered through interviews, field observations, and the review of supporting documents, including transcripts of discussions. The findings reveal that digital payments at the Grand Hyatt Bali provide convenience to guests in conducting transactions such as transaction speed, recording accuracy, and ease in the verification process. However, the use of digital payments also has a negative impact where digital cash receipts are recorded in the accounts receivable section requiring many supporting documents making it appear less optimal and less functional and highly dependent on the availability and stability of the internet network connection. From an internal control perspective, digital payments help improve transparency and accuracy in cash recording processes. The risk of miscalculations or data manipulation is reduced because transaction evidence is readily available digitally, in the form of sales slips, system notifications, and account statements. The mechanism of internal supervision regarding cash inflows at Grand Hyatt Bali Hotel based on COSO consists of several components, namely the organizational climate, monitoring practices, hazard analysis, exchange of insights and knowledge, and supervision. Overall, the implementation of internal controls has been carried out by all staff, however, the implementation is still not optimal related to the collection of documents that are still late, this is caused by staff knowledge about the documents required when digital payments are still not executed according to the procedures outlined in the SOP.